Are There Austerity-Related Policy Changes in Germany? - Werner Eichhorst; Anke Hassel (Institute for the Study of Labor (IZA), 2015)
This paper assesses the existence and the extent of austerity-oriented policies in Germany in the aftermath of the 2008-9 recession. In contrast to the intensive phase of labour market and welfare state reforms in the early 2000s aimed at 'welfare readjustment', we do not see austerity policies in Germany, rather a continuation of the path that was adopted earlier. This can be explained by the economic conditions which were, and still are, much more favourable than in many other EU Member States. Most recently, we can identify a partial reregulation of the labour market, most notably the introduction of a national minimum wage, a potential increase in the regulation of non-standard contracts and a reintroduction of early retirement for labour market insiders. These policies can be classified as 'welfare protectionism'.
Keywords: J21; J26; J68; 330; labour market reforms; Germany; austerity; welfare state retrenchment